A functional SNP regulated by miR‐196a‐3p in the 3′UTR of FGF2 is associated with bone mineral density in the Chinese population. Issue 6 (13th April 2017) - Zhu, Dong‐Li; Guo, Yan; Zhang, Yan; Dong, Shan‐Shan; Xu, Wen; Hao, Ruo‐Han; Chen, Xiao‐Feng; Yan, Han; Yang, Shui‐Yun; Yang, Tie‐Lin
Abstract : In this study, we firstly investigated the associations between SNPs in FGF2 and BMD in Han Chinese populations. We identified one SNP rs1048201: C > T in FGF2 > 3′UTR significantly associated with spine BMD ( P = 1.53×10 –3 ). Our study also provided evidence that SNP rs1048201: C > T variant may act by affecting binding of hsa‐miR‐196a‐3p. The SNP‐modified posttranscriptional gene regulation by miRNA could be a potentially pathogenetic mechanism of osteoporosis. Abstract: Previous studies have identified FGF2 as a susceptibility gene for osteoporosis in Caucasians. Evaluating the genetic associations in different ethnicities is necessary. Moreover, elucidating the functional mechanism for the susceptibility loci is important to offer new targets for therapeutic studies. Here, we genotyped 10 SNPs in FGF2 and tested for associations with bone mineral density (BMD) in a discovery sample of 1, 300 Chinese subjects. Nominally significant results were subjected to replication in another sample of 1, 039 Chinese subjects. We identified one SNP rs1048201:C>T in FGF2 3′untranslated region significantly associated with spine BMD (combined cohorts, P = 1.53×10 −3 ). Expression quantitative trait locus analyses revealed that rs1048201 also affected FGF2 gene expression ( P = 7.03×10 −4 ). Bioinformatics prediction suggested that rs1048201 T allele could disrupt miRNA binding. Luciferase assay validated that the C allele had a repressive effect on FGF2 gene expression. We found that hsa‐miR‐196a‐3p affected expression on both mRNA and protein levels of FGF2 . In conclusion, our study provided evidence that a functional SNP rs1048201 was associated with BMD, and SNP rs1048201:C>T variant may act by affecting binding of hsa‐miR‐196a‐3p. The SNP‐modified posttranscriptional gene regulation by miRNA could be a potentially pathogenetic mechanism of osteoporosis.